Study of the Long-Term Deformation Characteristics of Municipal Sludge Solidified Soil under the Coupling Action of Dry-Wet Cycles and Initial Static Deviatoric Stress. (11th November 2020) - Yang, Aiwu; Yang, Shaokun; Xu, Guofang; Zhang, Wei
Abstract : A self-developed curing agent is used to solidify the municipal sludge taken from Tianjin. Then, the long-term deformation characteristics of the sludge solidified soil are investigated by means of unconsolidated undrained creep tests with different dry-wet cycles for considering the influence of climate. The experimental results show that the attenuation rate of the shear peak strength of municipal sludge solidified soil decreases gradually with the increase of the number of dry-wet cycles, and the strength remains unchanged when the number of dry-wet cycles is greater than 10. The variation laws under different initial static deviatoric stresses are basically identical. When the applied stress is less than the yield stress of the sludge solidified soil, the duration curves of creep show only attenuated stage, i.e., with very small deformation, and the deformation reaches a constant in a short period of time. When the deviatoric stress reaches the long-term strength of the soil, the instantaneous deformation of the sludge solidified soil becomes large and damage occurs quickly. Under the same deviatoric stress, the creep deformation increases with the increase of the number of dry-wet cycles. When the load applied in each step is of the same magnitude, the higher the initial static deviatoric stress is, the larger the deformation of sludge solidified soil will be. It is found that the stress-strain relationship and the relationship between creep strain and time can be well described by an exponential function and a hyperbolic function, respectively. On this basis, a creep model is proposed for the long-term deformation considering the effect of dry-wet cycle times and initial static deviatoric stress. The model is further validated by comparing the predictions with the test results under different deviatoric stresses; the good agreement between which shows the potential application of the model to relevant practical engineering.